Enterococcus faecium secreted the NlpC/P60 family protein to enhance host immunity and indirectly increases Akkermansia muciniphila for slowing aging - Guo, Yinrui; Zou, Shiqi; Yang, Xieqing; Li, Ran; Fu, Weiqi; Xu, Changqiong; Zhang, Fang; Yang, Xin (Frontiers in Microbiology, 2026)
While probiotics like Enterococcus faecium are known for gut health benefits, their potential anti-aging effects are poorly understood. This study investigated whether E. faecium fermentation broth delays aging and explored its mechanisms. Using a mouse model, lifespan assays suggested that the E. faecium fermentation broth may contribute to lifespan extension, indicating anti-aging properties. Microbiome analysis showed it modulated gut microbiota, increasing beneficial Akkermansia abundance. Key active components identified included myo-inositol (promoting hair follicle growth), D-ribose, and secreted proteins. While myo-inositol increased the abundance of Lactobacillus reuteri and Lactobacillus johnsonii, it did not increase Akkermansia. A high-content secreted protein, NlpC/P60, present in E. faecium fermentation broth, may enhance host immunity through the NOD-like receptor signaling pathway, thereby restricting pathogen colonization and reshaping the gut microbiota. This immune boost indirectly elevated levels of beneficial bacteria like Akkermansia muciniphila and L. johnsonii, improving overall microbiota composition and mitigating age-related diseases. The findings demonstrate that E. faecium fermentation broth combats aging through multiple pathways, primarily microbiota modulation and immune enhancement. The identification of NlpC/P60 as a key mediator provides crucial mechanistic insight. This study elucidates the material basis and pathways by which E. faecium fermentation broth delays aging, offering experimental support for developing novel microecological therapies against age-related diseases.